2021
DOI: 10.1108/ijoa-12-2020-2535
|View full text |Cite
|
Sign up to set email alerts
|

Mindfully performed organisational routines: reconciling the stability and change duality view

Abstract: Purpose The purpose of this paper is to provide a process model on how mindfully performed organisational routines can simultaneously enable organisational stability and organisational change. Design/methodology/approach Via conceptual analysis, the authors develop several propositions and a process model integrating the theory of mindfulness and performative aspects of organisational routines with organisational stability and change. To do so, the authors review the literature on organisational routines, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…In fitting conditions, TVs communicate efficiently and support trust in their organization (Quade et al, 2020, Velez-Calle et al, 2020. Research shown that under good conditions, virtual communication is suitable for VTs operation and performance; but the process of adaptation and support needs to be in place (Shaik et al, 2021). Thus, this study resulted in accordance with Aranaz-Andrés et al (2021), Ipsen et al (2021 showing virtual technologies may result into work-life balance issues.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In fitting conditions, TVs communicate efficiently and support trust in their organization (Quade et al, 2020, Velez-Calle et al, 2020. Research shown that under good conditions, virtual communication is suitable for VTs operation and performance; but the process of adaptation and support needs to be in place (Shaik et al, 2021). Thus, this study resulted in accordance with Aranaz-Andrés et al (2021), Ipsen et al (2021 showing virtual technologies may result into work-life balance issues.…”
Section: Discussionsupporting
confidence: 76%
“…In such environment, it was explained that the management needs to have full control over the process and work tasks, and each VT member have to work independently on each one´s part of a task (Lukić & Vračar, 2018). The final production is then processed by another team, as periodically seen in key projects, such as national security (Tenopir et al, 2011). Moreover, a common vision and aim is the key as it significantly stimulates each team and also improves trust among VT members and leadership.…”
Section: Strategies To Enhance Performance Of Vtsmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that digital transformation can initiate new ways of obtaining information and knowledge, thus influencing decisions and changes in aspects such as structure and/or behavior. On the other hand, organizational routines can halt change [58], thus influencing the result of organizational transformation led by digital technologies. Organizational routines influence the use of technology (e.g., [59]), and so digital transformation alters how technologies influence routines, which may alter its potential.…”
Section: Organizational Routines and How They Can Influence Organizat...mentioning
confidence: 99%